Effect of MA-g-PP addition on mechanical properties of polypropylene/hollow glass spheres/nanoclay composites - Gumus, Beril Eker (SPRINGER, 2023)
The purpose of this study was to investigate the effect of maleic anhydride-grafted polypropylene (MA-g-PP) loading on the mechanical and physical properties of polypropylene/glass spheres/montmorillonite nanoclay (PP/HGS/MMT) composites. Polypropylene-based composite samples consisted of 10 wt% HGS and 5wt% MMT. MA-g-PP in five different weight fractions of (0, 2.5, 5, 7.5, and 10 wt%) was added to PP/HGS/MMT composites to produce samples as well. Elasticity modulus, tensile strength, % elongation, Izod impact strength, hardness, and density were determined for each sample. From the results of tests, increasing Ma-g-PP content increased the elastic modulus and tensile strength. On the other hand, impact resistance, elongation at break, density, and hardness of composites decreased with increasing Ma-g-PP content. Furthermore, the structure of composites was investigated by scanning electron microscopy, and Fourier transform infrared spectroscopy was carried out in order to determine the chemical bonds of the composites. In addition to this, physical tests were applied such as melt flow index (MFI), moisture content (MC), vicat softening temperature (VST), heat deflection temperature (HDT), limit oxygen index (LOI). The results obtained show that HDT, VST, MFI, and LOI decreased gradually as the MA-g-PP content increased from 0 to 10 wt%. On the other hand, MC increased with the increase in the MA-g-PP content from 0 to 10 wt%.
Keywords: Maleic anhydride-grafted polypropylene; Montmorillonite nanoclay; Glass spheres; Polypropylene; Mechanical properties; CLAY NANOCOMPOSITES; COUPLING AGENT; MORPHOLOGY; Polymer Science